Turner Prize 2000 : Tate Britain. - Tate Britain, Londen (Londen : Tate Trustees, 2000)
Brown, Glenn ; Raedecker, Michael ; Takahashi, Tomoko ; Tillmans, Wolfgang
Turner Prize 2000, Tate Britain, Londen, 25 October 2000 - 14 January 2001
kunstcatalogus